PENGARUH REWARD, PUNISHMENT DAN MOTIVASI TERHADAP KINERJA MITRA PENGEMUDI SHOPEE FOOD YOGYAKARTA - Anugra Saputra , Angga; Robi’ Nurwahyudi, Muhammad (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2024)
This research aimed to determine the effect of reward, punishment and motivation on the performance of Shoppe food driver partners in Yogyakarta. The research method used is a quantitative descriptive method with 35 drivers as the population. The results showed that reward and motivation have a positive and significant effect on the performance of Shoppe Food drivers in Yogyakarta. Furthermore, the accumulation of all variables on the performance of Shoppe Food drivers showed positive and significant results. This research expects to be used as material for evaluating Shoppe Food management in managing the performance of Shoppe Food drivers in Yogyakarta.